Two-phase flow pattern based theoretical study of loop heat pipes. (5th April 2016) - Weng, Chih-Yuan; Leu, Tzong-Shyng
Highlights: A new two-phase flow pattern based theoretical modeling is proposed for LHP. The proposed LHP model is for condensation tube diameter design ranging from 1 to 5 mm. MAPE of LHP compensation chamber temperature shows only 2.00% in FCM operation mode. More detailed characteristics within LHP can be obtained by the proposed model. Abstract: Loop heat pipes (LHPs) are passive heat transport devices using capillary structures to circulate the working fluid. In this study, several theoretical models based on conservation equations in the system are used to evaluate the characteristics of LHPs. In addition, while computing the characteristics of two-phase flow within LHP, the progression of the flow regimes in the condensing tube is specially considered by adopting proper two-phase flow pattern map. In this study, the comparison between the experimental and theoretical results of new proposed model achieves the smallest mean absolute percentage error (MAPE) of 2.00% in the fixed conductance modes among all existing models. It has been shown that the characteristics of LHP can be better predicted by using new proposed model with consideration of the surface-tension influence on two-phase flow pattern map within condensation tube diameter ranging from 1 mm to 5 mm.